2023
DOI: 10.1097/ccm.0000000000005801
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Paradox and Functional Outcomes in Sepsis: A Multicenter Prospective Study

Abstract: OBJECTIVES: In Asian populations, the correlation between sepsis outcomes and body mass is unclear. A multicenter, prospective, observational study conducted between September 2019 and December 2020 evaluated obesity’s effects on sepsis outcomes in a national cohort. SETTING: Nineteen tertiary referral hospitals or university-affiliated hospitals in South Korea. PATIENTS: Adult patients with sepsis (n = 6,42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…Our previous work has also shown that an obesity paradox exists in severe pneumonia or acute respiratory failure requiring extracorporeal oxygenation membrane support (2,3). From these findings, it is evident that the potential benefits of this paradox derive from two aspects of a high BMI, that related to muscle mass and that related to adipose tissue.…”
mentioning
confidence: 90%
See 3 more Smart Citations
“…Our previous work has also shown that an obesity paradox exists in severe pneumonia or acute respiratory failure requiring extracorporeal oxygenation membrane support (2,3). From these findings, it is evident that the potential benefits of this paradox derive from two aspects of a high BMI, that related to muscle mass and that related to adipose tissue.…”
mentioning
confidence: 90%
“…Numerous studies have consistently demonstrated that obese patients with sepsis tend to have better survival rates than those nonobese patients, suggesting a potential protective effect of excess body weight (1). In addition to Western populations, recent research conducted by Yeo et al (2) indicated that obese Asian patients with sepsis may also benefit from a similar survival advantage. In their study, obesity was associated with better in-hospital survival and functional outcomes at discharge.…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the proportion of muscle mass to body mass is more prognostic in extremely critical illnesses (2). This year’s data, published in Critical Care Medicine , consistently showed that obesity (high BMI) protects against functional loss in sepsis survivors, leading to better survival rates (4). However, the priority afforded a lack of muscle mass or the fat mass ratio in the data needs to be clarified (4), with support for this hypothesis provided by evidence of the impact of a high BMI on sarcopenia and the clinical outcome of severe disease.…”
mentioning
confidence: 99%